Proposed Marketing Concepts Using the Conjoin Method in MSMEs Sego Berkat Bu Murni - Hesti Dita Pramesti; Rizqa Amelia Zunaidi (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
The food industry in Indonesia is one of the sectors that support the value of the national investment. However, in 2020 the food industry experienced a decline in growth during the Covid-19 pandemic and was slowly able to increase steadily in 2021. Bu Murni's Sego Berkat is one of the food industries that has also experienced declining income during the COVID-19 pandemic. The difficulty of MSMEs is changing the increase in income due to new competitors during the Covid-19 pandemic. The purpose of this study is to provide a proposed marketing concept that suits the preferences of Sego Berkat MSME consumers based on place, price, and promotion factors. This research data was obtained through the distribution of questionnaires to Sego Berkat MSME customers, and the questionnaire results will be calculated as the weight of interests of each level and attributes using conjoin analysis. The results of the conjoin analysis resulted in a proposed marketing concept by the preferences of Sego Berkat MSME consumers and is to carry out sales promotion with the type of promotion buy 3 get 1, the price applied with a range of Rp. 15,000 – Rp. 19,000 on online and offline purchases.